Peningkatan Self Awareness Diabetes Melitus di Desa Simpur, Jabiren Raya, Kabupaten Pulang Pisau, Provinsi Kalimantan Tengah - Ester Inung Sylvia; Gad Datak; Andre Febrian; Thomas Jhonson (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Diabetes mellitus is one of four diseases that cause death worldwide. Central Kalimantan is in 23rd position out of 34 provinces for the incidence of Diabetes with a prevalence of 1.14%. One of the districts in Central Kalimantan, namely Pulang Pisau District, shows that the prevalence of DM exceeds the provincial prevalence, namely 1.20%. The data shows that many factors influence one of them is the level of public awareness of diabetes.The aim of this community service activity is to increase the community's self-awareness through education. The activity was carried out in Simpur Village, Jabiren Raya, Pulang Pisau Regency with a total of 30 participants. Activities are carried out by filling out a pretest questionnaire, health education and posttest. The results show an increase in DM Self Awareness in the community. The average self-awareness score before education was 66.73 and after education was 80.00. The statistical test results show that there is a significant difference in the average self-awareness score between before and after education with a p value of 0.005 and a mean difference of 13.27.With this activity, it is hoped that in the long term, people can increase their self-awareness of diabetes so that they can prevent the occurrence of diabetes or an increase in complications from diabetes mellitus.